Strategy to Accelerate the Resolution of Village Boundary Determination and Confirmation in Nunukan Regency - Eradias Elias; Hasniaty; Muhammad Ridwan Arif (Pustaka Digital Indonesia, 2025)
This study aims to formulate the most recommended strategy for the Community and Village Empowerment Office of Nunukan Regency in an effort to accelerate the completion of Village Boundary Determination and Confirmation (PPBDes) in Nunukan Regency to achieve the target of 100% of 232 villages and 8 sub-districts. This study uses a mixed method with an exploratory design variant of the instrument development model. This model is to develop and implement quantitative instruments (IFE, EFE and QSPM) based on previous qualitative findings (SWOT). Data collection in this study was carried out through interviews, observations, questionnaires and online data collection. The results of this study found internal and external factors that influence the implementation of PPBDes in Nunukan Regency. Furthermore, based on the results of the IFE and EFE questionnaires, it was found that the weakness factor had the highest score with a score of 3.86, followed by the strength factor with a score of 3.76, then the opportunity factor with a score of 3.67 and finally the threat factor with a score of 3.62. Based on internal and external factors, a SWOT analysis was conducted to formulate strategies that could be taken to accelerate the completion of PPBDes in Nunukan Regency, then continued by using the QSPM analysis instrument to determine which strategy was most recommended or prioritized for implementation in an effort to accelerate the completion of PPBDes in Nunukan Regency.